Social innovation in generating income of community through marketing the traditional cookies / Marzlin Marzuki ... [et al.] - Marzuki, Marzlin; Wan Omar, Maznah; Ibrahim, Syazliyati; Ismail, Jurina (2018)
Thriving for economic sustainability in the current depressing economy is the key concern among middle and low income community, particularly those who are living in the area of Merbok, Kedah, Malaysia. Having skills particularly in producing homemade cookies should not be limited to personal consumption alone. With innovative and creative ideas, these skills should be nurtured and polished together with marketing skills to move ahead in the economic ladder. A study was conducted via a community project to garner social innovation ideas that can enhance the economic wellbeing of the Merbok community. A project was undertaken by a group of academicians with multiple academic backgrounds together with a community nearby the campus. The Merbok community was chosen as there are many low income families including the single mother community who reside in this area. The aim of the project was to assist the low income community to generate higher level income through the marketing of traditional cookies. The objective of this project was achieved through transferring of knowledge particularly in giving assistance by creating a competitive branding and labelling of the traditional cookies. Nevertheless, the application of information technology to social media marketing, as well as knowing how to keep the necessary accounting records is a must to succeed in the current marketing competition. This project is based on in-depth teaching and learning process by first educating the community in terms of marketing the traditional cookies to generate income for the community. With the help of ‘Jawatankuasa Kemajuan dan Keselamatan Kampung (JKKK)’ which acted as the social entrepreneur and moderator of the program, we managed to help the community by marketing the traditional cookies as well as transferring our knowledge and expertise to the community.